British Association of Urological Surgeons (BAUS) consensus document for the management of male genital emergencies – penile amputation. (25th March 2018) - Shukla, Chitranjan J.; Brown, Gareth; Dorkin, Trevor; Lucky, Marc; Pearcy, Richard; Rees, Rowland W.; Shabbir, Majid; Summerton, Duncan J.; Muneer, Asif; ,
Abstract : Male genital emergencies relating to the penis and scrotum are rare and require prompt investigation and surgical intervention. Clinicians are often unfamiliar with the management of these conditions and may not work in a specialist centre with on‐site expertise in genitourethral surgery. A series of consensus statements have been developed by an expert consensus committee comprising members of the British Association of Urological Surgeons (BAUS) Section of Andrology and Genitourethral Surgery together with experts from urology units throughout the UK. Penile amputation is a rare genital emergency, which requires prompt intervention and microsurgical reconstruction. The consensus statements will outline the management of these cases for non‐specialist units, as well as recommendations for reconstruction for specialists.